The thermally induced decarboxylation mechanism of a mixed-oxidation state carboxylate-based iron metal–organic framework. Issue 85 (30th September 2019) - Drake, Hannah F.; Day, Gregory S.; Vali, Shaik Waseem; Xiao, Zhifeng; Banerjee, Sayan; Li, Jialuo; Joseph, Elizabeth A.; Kuszynski, Jason E.; Perry, Zachary T.; Kirchon, Angelo; Ozdemir, Osman K.; Lindahl, Paul A.; et al.
Abstract : The thermally generatable decarboxylation activation pathway of a carboxylate-based Iron MOF is reported; cluster and gas sorption changes are characterized. Abstract : Investigations into a thermally generated decarboxylation mechanism for metal site activation and the generation of mesopores in a carboxylate iron-based MOF, PCN-250, have been conducted. PCN-250 exhibits an interesting oxidation state change during thermal treatment under inert atmospheres or vacuum conditions, transitioning from an Fe(iii )3 cluster to a Fe(ii )Fe(iii )2 cluster. To probe this redox event and discern a mechanism of activation, a combination of thermogravimetric analysis, gas sorption, scanning electron microscopy, 57 Fe Mössbauer spectroscopy, gas chromatography-mass spectrometry, and X-ray diffraction studies were conducted. The results suggest that the iron-site activation occurs due to ligand decarboxylation above 200 °C. This is also consistent with the generation of a missing cluster mesoporous defect in the framework. The resulting mesoporous PCN-250 maintains high thermal stability, preserving crystallinity after multiple consecutive high-temperature regeneration cycles. Additionally, the thermally reduced PCN-250 shows improvements in the total uptake capacity of methane and CO2 .